Breast Specific Gamma Imaging (BSGI)/ Molecular Breast Imaging (MBI) - Rajchadara, Samart (The Bangkok Medical Journal, 2012)
Breast cancer is one of the most frightening cancers for women because of its high incidence: it is the most common cancer in Thai females. Genetic and environment are both important causative factors, especially the latter. Changing life styles, and increased use of drugs and food supplements have contributed towards the increasing incidence of breast cancer. Early detection of cancer may lead to successful treatment and a longer life span. Teaching women how to examine their own breasts is recommended worldwide to detect abnormal breast mass and cancer. However, the size of the lump, different examination techniques and density of the breast also play a role in detectability.